Nomenclatural novelties and typification of names in Scorzonera sensu lato (Asteraceae, Cichorieae) for the Italian vascular flora - Bartolucci, Fabrizio; Galasso, Gabriele; Conti, Fabio (Phytotaxa, 2020)
According to recent molecular study, the genus Scorzonera sensu lato is polyphyletic. A revised circumscription of this genus was proposed with the recognition of seven genera: Scorzonera sensu stricto, Gelasia, Lipschitzia, Pseudopodospermum, Pterachaenia, Ramaliella, and Takhtajaniantha. Accordingly, a taxonomic treatment of the genus Scorzonera sensu lato for the Italian vascular flora is presented. Nomenclatural types for six names are designated here: Scorzonera calcitrapifolia var. decumbens, S. columnae, S. deliciosa, S. neapolitana, S. trachysperma var. undulata, and S. villosa. Furthermore, the following new combinations are proposed: Gelasia villosa subsp. columnae, Pseudopodospermum hispanicum subsp. asphodeloides, P. hispanicum subsp. neapolitanum, and P. undulatum subsp. deliciosum.